S30 The feasibility of investigating methylphenidate for the treatment of sarcoidosis-associated fatigue (the FaST-MP study) – a double-blind, parallel-arm randomised controlled-trial. (12th November 2019) - Atkins, CP; Jones, AP; Wilson, AM
Abstract : Aim: We aimed to investigate the feasibility and optimum design of a study to determine the clinical efficacy of symptomatic treatment of sarcoidosis-associated fatigue using methylphenidate. Methods: Patients with pulmonary sarcoidosis and significant fatigue were recruited from the respiratory clinic at a single hospital, into a parallel-arm, double-blind, placebo-controlled randomised-controlled trial, with referrals from other participant identification centres in the region. Fatigue was quantified using the Fatigue Assessment Scale (FAS) questionnaire. Eligible participants were randomised in a 3:2 ratio in favour of methylphenidate through an online system using block randomisation controlled for baseline fatigue severity. Methylphenidate was commenced at 10 mg (1 capsule) twice daily, increased to 20 mg (2 capsules) twice daily if appropriate after 2 weeks. Participants attended up to seven visits over a period of up to 24 weeks, with follow-up questionnaires six weeks after completing medications. Participants allocated to placebo received identical placebo capsules and attended the same visit schedule. Results: A total of 385 patients were screened; 56 (14.5%) were eligible and 23 (5.9%) consented to participate, of which 22 received their allocated intervention. No withdrawals occurred although one participant receiving methylphenidate discontinued the intervention due to an adverse event. Adverse events observed were similar between groups. No difference in fatigue scores between groups was seen at any point (figure 1), although the mean fatigue score in each group improved from baseline. In the placebo group, improvements in non-fatigue clinical measures (anxiety, respiratory symptoms, perceived health and overall quality of life) were seen compared with the methylphenidate group. Conclusions: The data from the FaST-MP study supports the feasibility of performing a trial powered to determine the clinical efficacy of methylphenidate for sarcoidosis-associated fatigue, although only a small proportion of patients with sarcoidosis and chronic fatigue would be eligible for such an intervention. The number of visits and amount of contact with the research team may have meant that the placebo arm did not represent 'usual care', possibly explaining the improvement in fatigue seen in the placebo group compared with baseline scores and the lack of difference between groups. Trial Registration – Clinicaltrials.gov NCT02643732